Efektivitas Terapi Murotal dan Relaksasi Benson terhadap Tingkat Kecemasan Pasien Pre Operasi Katarak di Poliklinik Mata Rumah Sakit Pertamina Prabumulih - Ratna Sari Dinaryanti; Nopi Astuti (Poltekkes Kemenkes Padang, 2023)
Cataracts are a condition of clouding of the lens that occurs due to hydration of the lens, denaturation of lens proteins. Cataract healing with surgery is an act that causes anxiety. Treatment for patient anxiety before cataract surgery with murotal therapy and benson relaxation is given for 15 minutes. The aim of this study was to determine the effectiveness of Murotal Therapy and Benson Relaxation on the Anxiety Level of Pre-Cataract Surgery Patients at the Eye Specialist Polyclinic, Pertamina Prabumulih Hospital. The research used Quasi Experimental with a pretest-posttest design without control design. The research sample consisted of 36 people, namely 18 people were given murotal therapy and 18 people were given Benson relaxation using a purposive sampling technique. The instrument used to measure anxiety uses the HARS questionnaire sheet. The results of the independent t test on the level of anxiety after being given the intervention of murotal therapy and Benson's relaxation obtained a p value of 0.162 (p>0.05) meaning that there was no significant difference between the administration of murotal therapy and Benson's relaxation. In conclusion murotal therapy and benson relaxation have the same effect on reducing anxiety levels. It is suggested that Benson's murotal therapy and relaxation can be applied to reduce anxiety levels in preoperative patients.